Ulama dan Gerakan Revivalis Islam di India Antara 1700- 1850 an - Mohamed Dali, Azharudin (Jurnal Usuluddin, 2002)
This article attempts to examine the relationship between the ulama and Islamic revivalist movement in 18 and 19th centuries India. The period was very crucial to the Muslims societies due the emergence of British as new master in the Indian Subcontinent following the fall of Mughal Empire. The Muslim faced drastic changes in their life, economically, socially and politically. As a guardian of Islam, the ulama undoubtedly played a vital part and were involved directly with the revivalist movement in India. The role of the ulama such as Shah Waliullah and Sayid Ahmad Barelvi were important to be highlighted to analyze the nature of the relationship between the ulama and the revivalist movements.